Changes in Hydrogen Sulfide in Rats with Hepatic Cirrhosis in Different Stages - 张宁;郑勇;陈卫刚;李睿;宋丽秀;徐丽红;徐可树 (Current medical science, 2017)
This study aimed to observe changes in the hydrogen sulfide（H_2S） system in the blood and liver tissue of rats with hepatic cirrhosis at different stages by studying the effect of H_2S on the course of hyperdynamic circulation in rats with hepatic cirrhosis. H_2S concentration in the blood from the portal vein and inferior vena cava of hepatic cirrhosis rat model induced with carbon tetrachloride was detected on the 15 th, 30 th, and 52 nd day. The expression of cystathionine β-synthase（CBS） and cystathionine γ-lyase（CSE） protein, and CBS and CSE mRNA in the liver was detected by immunohistochemistry and reverse transcriptase polymerase chain reaction（RT-PCR）, respectively. The results indicated that H_2S concentration in the blood from the portal vein and inferior vena cava of rats with hepatic cirrhosis was significantly lower than that in the control group. H_2S was gradually decreased with the development of the disease and significantly lower in the blood from portal vein than in the blood of inferior vena cava at the mid-stage and the late stage groups. The expression levels of CBS and CSE protein, and CBS and CSE mR NA in the livers with hepatic cirrhosis at different stages were all higher than those in the control group, and the expression gradually increased with the development of the disease. The expression of CBS was lower than CSE in the same stages. The results indicated that the CSE mRNA was expressed predominantly in the cirrhosis groups as compared with CBS mRNA. Among experimental rats, the H_2S system has an important effect on the occurrence and development of hyperdynamic circulation in rats with hepatic cirrhosis. This finding adds to the literature by demonstrating that H_2S protects vascular remodelling in the liver, and that CSE is indispensable in this process.